An Alabaster Box - Freeman, Mary Eleanor Wilkins, 1852-1930; Kingsley, Florence Morse, 1859-1937; Mulford, Stockton, 1886-1960 (Salt Lake City, UT : Project Gutenberg, 2006)
"An Alabaster Box" by Mary Eleanor Wilkins Freeman and Florence Morse Kingsley is a novel written in the early 20th century. The story is set in a small village, Brookville, where a young minister, Wesley Elliot, struggles to pay his bills and establish his place in the community amidst the backdrop of a church fair designed to raise funds for his salary. The novel explores themes of love, ambition, and the clash between tradition and modernity through its rich characters, including the determined Mrs. Solomon Black and the mysterious newcomer Lydia Orr. The opening of the novel introduces us to Wesley Elliot, who is facing financial difficulties while trying to fulfill his ministerial duties. As he navigates his responsibilities in the church and the expectations of his congregants, he is drawn into a church fair led by Mrs. Black, aimed at raising funds for him. Wesley's internal dilemmas about his ambitions and the emotional pull he feels toward Fanny Dodge, a local girl seemingly interested in him, create tension. Notably, the arrival of Lydia Orr brings intrigue to the small town, as she unexpectedly purchases the entire church fair, raising questions about her background and intentions. This intriguing mix of personal struggles and communal dynamics sets the stage for a deeper exploration of the characters' lives. (This is an automatically generated summary.)
Release date is 2006-04-10
Jeff Kaylin and Andrew Sly
Keywords: New England -- Social life and customs -- Fiction